Opportunities and risks: a case study of young urban children’s online life in China - Kongchao He; Guoqiang Ying; Xiaoping Yang (Problemy Wczesnej Edukacji)
It is a common phenomenon in China that 9-12 year old children spend a lot of time on the internet. From this study, it can be concluded that the time children spend online is different between boys and girls, and that boys tend to stay online much longer. In addition to this, the sites where children access the internet are not fixed, while children believe that the internet is safe and has brought them benefits. At the same time, some children showed their dependence on the internet. The top three behaviors of children’s online life are information searching, chatting and making friends, and playing games. The internet is not only a pleasurable experience for children but also troublesome. Most  of the children’s online life is under adult supervision. Based on these results, it is believed that online life has brought convenience and developmental opportunities to young Chinese children, facilitating their learning and relaxation, but at the same time bringing them risks and crisis, especially the pain resulting from unsuitable content, exposure of privacy and internet addiction.